Clonal hybrids of the common laboratory fish Fundulus heteroclitus. - Dawley, R M (1992)
All-female hybrids of the killifishes Fundulus heteroclitus and Fundulus diaphanus, known from two sites in Nova Scotia, Canada, are shown to reproduce clonally. Isozyme analysis of crosses between female hybrids and male F. heteroclitus reveals that their progeny are genetically identical and show no evidence of recombination or paternal inheritance. Flow cytometric measurement of DNA content shows the hybrids to be diploid, with DNA values intermediate to those of the parental species. Because they are related to F. heteroclitus, a fish used widely as a model organism in experimental biology, the clonal hybrids are potentially valuable for experimental studies requiring subjects with a constant genetic background. In addition, the discovery of unisexuality and cloning in a fish whose reproductive physiology and development are so well characterized provides a unique opportunity to examine the underlying causes of clonal reproduction in vertebrates.